Alteration of gastric microbiota and transcriptome in a rat with gastric intestinal metaplasia induced by deoxycholic acid - Xu, Zijing; Xiao, Ling; Wang, Shuaishuai; Cheng, Yuqin; Wu, Jianping; Meng, Yufen; Bao, Kaifan; Zhang, Junfeng; Cheng, Chun (Frontiers in Microbiology, 2023)
Objective Bile reflux plays a key role in the development of gastric intestinal metaplasia (GIM), an independent risk factor of gastric cancer. Here, we aimed to explore the biological mechanism of GIM induced by bile reflux in a rat model. Methods Rats were treated with 2% sodium salicylate and allowed to freely drink 20 mmol/L sodium deoxycholate for 12 weeks, and GIM was confirmed by histopathological analysis. Gastric microbiota was profiled according to the 16S rDNA V3–V4 region, gastric transcriptome was sequenced, and serum bile acids (BAs) were analyzed by targeted metabolomics. Spearman's correlation analysis was used in constructing the network among gastric microbiota, serum BAs, and gene profiles. Real-time polymerase chain reaction (RT-PCR) measured the expression levels of nine genes in the gastric transcriptome. Results In the stomach, deoxycholic acid (DCA) decreased the microbial diversity but promoted the abundances of several bacterial genera, such as Limosilactobacillus, Burkholderia–Caballeronia–Paraburkholderia, and Rikenellaceae RC9 gut group. Gastric transcriptome showed that the genes enriched in gastric acid secretion were significantly downregulated, whereas the genes enriched in fat digestion and absorption were obviously upregulated in GIM rats. The GIM rats had four promoted serum BAs, namely cholic acid (CA), DCA, taurocholic acid, and taurodeoxycholic acid. Further correlation analysis showed that the Rikenellaceae RC9 gut group was significantly positively correlated with DCA and RGD1311575 (capping protein-inhibiting regulator of actin dynamics), and RGD1311575 was positively correlated with Fabp1 (fatty acid-binding protein, liver), a key gene involved in fat digestion and absorption. Finally, the upregulated expression of Dgat1 (diacylglycerol acyltransferase 1) and Fabp1 related to fat digestion and absorption was identified by RT-PCR and IHC. Conclusion DCA-induced GIM enhanced gastric fat digestion and absorption function and impaired gastric acid secretion function. The DCA–Rikenellaceae RC9 gut group–RGD1311575/Fabp1 axis might play a key role in the mechanism of bile reflux-related GIM.